Human capital theory vs. screening hypothesis: Evidence from the Greek health sector - Stefanos Chanis; Constantine Tsamadias (SPOUDAI - Journal of Economics and Business, 2022)
This study tests whether the human capital theory is stronger than the screening hypothesis, using data from the Greek health sector. The paper estimates the rates of return of workers in the Greek health sector and tests the screening hypothesis. The evidence shows that the 'weak' version of the screening hypothesis is valid, but in general, the empirical results are consistent with the human capital theory.
Keywords: J24; I26; 330; Rate of Return; Human Capital; Screening Hypothesis; Greek Health Sector